HIV and innate immunity – a genomics perspective - Rausell, Antonio (Faculty of 1000 Ltd, 2013)
Innate immunity is a theme of increasing interest for HIV research. However, the term is overstretched to cover biological barriers, cellular systems, soluble factors, signaling pathways, and effectors and is inconsistently applied. A clearer semantic classification of the components of innate immunity is needed, which will have direct relevance to the interpretation of human genome variation. Here, we discuss genomic approaches that can assist in re-defining the perimeter of innate immunity. We place particular emphasis on the characteristics of effectors of the intracellular defense against HIV and other pathogens.